Porous activated carbon particles from rice straw waste and their adsorption properties - Nandiyanto, Asep Bayu Dani; Putra, Zulfan Adi; Andika, Riezqa; Muhammad Roil, Bilad; Kurniawan, Tedi; Zulhijah, Rizka; Hamidah, Ida (Taylor's University, 2017)
The purpose of this research was to synthesize porous activated carbon particles from rice straw waste and investigate their adsorption properties. Production of porous carbon particles involved several steps: (i) burning rice straw waste; (ii) ball-mill process; and (iii) the activation treatment. To achieve the optimum process in the activation treatment, the concentration of activating agent (i.e. potassium hydroxide) was varied. Experimental results showed that this method is effective to create porous carbon particles. Control of the porosity is also possible by managing the amount of activation agent (i.e. potassium hydroxide). The higher concentration of activation agent has a direct correlation to produce more cavities in the material. The study also confirms that the change in porosity has a direct impact to the ability of the product for adsorbing molecules. Since the present method is converting rice straw waste into useful and valuable porous carbon particles, further development of this study would give a positive impact for the reduction of rice straw waste emission.